Aspects of the evolutionary biology of the Proteaceae, with emphasis on the genus Leucadendron and its phylogeny - Midgley, Jeremy John (Department of Biological Sciences, 2026)
This genus is useful for a phylogenetic study because it comprises many species (79), is morphologically very diverse and appears to have diverged early on in the history of the family in Africa. Polarity of many characters was determined by outgroup analysis and the ontogenetic method. Exceptionally high levels of convergence made the determination of the phylogeny of the subsections problematic. An index, which is the sum of weight of all derived characters present in a species, was determined. The genus should be removed from its present subtribe, the Aulacinae, to be placed closer to the Leucospermum "alliance". I suggest an arid temperate, shrub-like origin for the African Proteaceae, which is in contrast to some published views. Modifications to accepted concepts of fruit homology for the family are presented. Also, further evolutionary trends in morphology, pollination and dispersal are indicated. 'The divergence index, if used as a "morphological clock", appears to be useful for further biogeographic and ecological analyses.